Avaliação da viabilidade da reciclagem de lodos de estação de tratamento de esgoto (LETE) e casca de arroz (CA) para a produção de blocos cerâmicos - Silva, Jaqueline Becker da (2023)
The population growth is directly related to the increased consumption of natural resources and the generation of waste resulting from human actions, among which sewage stands out, which is a heterogeneous mixture produced by water consumption. The sewage is conducted to the sewage treatment stations after its generation, where physical, chemical and biological processes take place that promote the reduction of its degree of contamination. During this process, a new waste is formed: WWTP sludge, which is characterized by high water and organic matter content, as well as the possible presence of heavy metals and pathogenic microorganisms. The growing concern with the environment and the final disposal of WWTP sludge encourages the search for alternatives for recycling this waste to produce new materials, since there is a great cost associated with the processing and disposal. The ceramic materials industry has great potential to incorporate wastes such as WWTP sludge and rice husk due to the high consumption of raw materials, similar composition of wastes and clays and the possibility of encapsulating heavy metals. Thus, this study aims to evaluate the incorporation of two WWTP sludges individually with different characteristics and rice husk together with the clay mass for the production of solid cubic ceramic bricks (30 × 30 × 30 mm). The production of the samples was carried out through an extrusion process. The experimental procedure was divided into two stages, the first evaluated the effect of adding WWTP sludge (SS-1 and SS-2) from different sources in replacement percentages of 0, 1, 2, 4, 6, and 10 % for brick production. In the second stage, the effect of adding SS-1 sludge (0, 2 and 6% by weight) and rice husks (0, 2 and 5% by volume) was evaluated. The physical and mechanical properties of the bricks were evaluated, such as apparent density, porosity, linear shrinkage, compressive strength and environmental analysis, and the values obtained compared with the requirements proposed by Brazilian standards. The incorporation of sludge in the mixture decreased the bulk density and increased water absorption. Properties such as resistance to compression and retraction were not significantly affected and met the requirements of Brazilian standards, in addition, several previously solubilized metals were encapsulated in the ceramic matrix after firing. The rice husk also affects some properties and acts as a pore-former inside the ceramic, and also contributes to the reduction of linear shrinkage. The experimental results indicate the viability of recycling wastewater treatment plant sludge and in natura rice husks for the production of extruded ceramic bricks.